Ab Initio Investigation of Structural, Electronic, and Thermoelectric Properties of ScPdBi Half-Heusler Alloy - Raad Edaan Haleoot; Ali Taher Mohi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Half-Heusler alloys have become an interesting research field due to their novel properties. The structural, electronic, dynamical stability, and thermoelectric properties of ScPdBi Half-Heusler alloy were studied using density functional theory. The calculated lattice constant of ScPdBi is in good agreement with theoretical and experimental work. The calculated formation energy reveals that ScPdBi is thermodynamically stable. The band structure shows semiconductor behavior with a direct band gap of 0.15 eV at the Gamma high symmetry point. The scandium atom (Sc) shows the major contribution to the density of states in the conduction band. The absence of negative vibrational modes in the phonon band structure is an indication of the mechanical stability of ScPdBi alloy. The transport properties were studied under different temperatures, where the Seebeck coefficient reaches -373 µV/K (322 µV/K) for p-type (n-type) at 300K, and a high power factor of 11.342×1011 Wm-1K-2s-1 is obtained at 1200K. Based on our results, the ScPdBi half-Heusler alloy is a stable semiconductor material with appropriate thermoelectric properties.
Keywords: Half-Heusler alloys; Density functional theory; Electronic properties; Thermoelectric properties